Table of Contents (Law, State and Telecommunications Review, 2025)
We are delighted to present a diverse collection of articles that delve into the impact of digital transformation in the legal field on data cybersecurity, problems and prospects of digitalisation in jurisprudence for cyber protection of information, addressing legal gaps in AI regulation for national security in Ukraine's defense sector, AI and telecommunication privacy with legal protections against algorithmic surveillance, mitigating security threats in sharing medical data, ethical and sustainable AI regulation in Colombia, comparative legal analysis of electronic government services to citizens and entities, latest criminalistic tools in cybercrime investigation from international and Ukrainian experience, problems of legal protection of trademarks on the internet in Kazakhstan, protection of cybercrime victims in the era of Industry 4.0, the right to privacy in the digital era through electronic surveillance in Cuban penal processes, the impact of artificial intelligence on electoral processes.